Evaluation of remodeling and geometry on the biomechanical properties of nacreous bivalve shells. - Muñoz-Moya, Estefano; García-Herrera, Claudio M; Lagos, Nelson A; Abarca-Ortega, Aldo F; Checa, Antonio G; Harper, Elizabeth M (Springer Science and Business Media LLC, 2022)
Mollusks have developed a broad diversity of shelled structures to protect against challenges imposed by biological interactions(e.g., predation) and constraints (e.g., [Formula: see text]-induced ocean acidification and wave-forces). Although the study of shell biomechanical properties with nacreous microstructure has provided understanding about the role of shell integrity and functionality on mollusk performance and survival, there are no studies, to our knowledge, that delve into the variability of these properties during the mollusk ontogeny, between both shells of bivalves or across the shell length. In this study, using as a model the intertidal mussel Perumytilus purpuratus to obtain, for the first time, the mechanical properties of its shells with nacreous microstructure; we perform uniaxial compression tests oriented in three orthogonal axes corresponding to the orthotropic directions of the shell material behavior (thickness, longitudinal, and transversal). Thus, we evaluated whether the shell material's stress and strain strength and elastic modulus showed differences in mechanical behavior in mussels of different sizes, between valves, and across the shell length. Our results showed that the biomechanical properties of the material building the P. purpuratus shells are symmetrical in both valves and homogeneous across the shell length. However, uniaxial compression tests performed across the shell thickness showed that biomechanical performance depends on the shell size (aging); and that mechanical properties such as the elastic modulus, maximum stress, and strain become degraded during ontogeny. SEM observations evidenced that compression induced a tortuous fracture with a delamination effect on the aragonite mineralogical structure of the shell. Findings suggest that P. purpuratus may become vulnerable to durophagous predators and wave forces in older stages, with implications in mussel beds ecology and biodiversity of intertidal habitats.